Candida parapsilosis endocarditis without vegetations at Echocardiography: a case report - Vargas-Herrera, Natalia (2024)
Candida endocarditis is a very serious manifestation of candida infections, and it has increased in incidence over the past years. Of these, C. parapsilosis has been described as a cause of endocarditis in native valves of intravenous drug users and prosthetic valves. We report the case of a female that developed a cerebrovascular accident secondary to emboli from aortic prosthetic valve C. parapsilosis endocarditis, despite apparently normal echocardiography. She received antifungal therapy without surgical intervention.